Key Technology and Development Prospect of Ontology Safety for Lithium-Ion Battery Storage Power Stations - Xiangyang XIA; Xinxin TAN; Zhouping SHAN; Hui LI; Zhiqiang XU; Jinbo WU; Jiahui YUE; Guiquan CHEN (Zhongguo dianli)
The introduction of the "dual carbon" targets and the ongoing advancement of low-carbon transitions in energy and electricity have posed significant challenges to the new-type power system, which primarily relies on renewable energy sources, particularly in terms of large-scale, safe, and efficient energy storage. In this context, energy storage stations, as a crucial component of the energy system, are of utmost importance in terms of safety management, directly influencing the stable operation and sustainable development of the entire power system. This essay delves into the current research status of lithium-ion battery safety management. Firstly, it systematically reviews the various battery health assessment methods widely used today and comprehensively summarizes the selection of health indicators in data-driven approaches. Secondly, it discusses the latest research hotspots in existing battery state assessment technologies from three perspectives: battery state evaluation based on data fragmentation, the construction of battery edge platforms, and intelligent inspection of energy storage stations. The essay also points out the future direction and key challenges of energy storage safety assessment. Lastly, it presents insights into the safety control technologies for energy storage stations, addressing the system stability considering battery parameter variations and the multi-objective control of energy storage systems.